Generalized confounded row–column designs. Issue 12 (18th June 2017) - Datta, Anindita; Jaggi, Seema; Varghese, Eldho; Varghese, Cini
ABSTRACT: Generalized Confounded Row–Column (GCRC) designs for factorial experiments have been introduced and methods of constructing GCRC designs have been discussed. Fractionally replicated GCRC designs have also been constructed. The designs obtained ensure balancing with respect to estimable effects.